2010
DOI: 10.1002/jhm.536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of clinician advice and patient preparedness to quit on subsequent quit attempts in hospitalized smokers

Abstract: BACKGROUND:Although smoking cessation counseling for cardiac inpatients is a quality measure, little data exist regarding postdischarge quit attempts in a primarily urban, African American, underserved population. This study aimed to assess preparedness to quit smoking and quit behaviors.METHODS:Smokers on the cardiology service were asked to rate preparedness using the 10‐step Contemplation Ladder. During phone surveys given 30‐days postdischarge, patients reported whether they made quit attempts, method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
2
11
0
2
Order By: Relevance
“…Baseline median score on the contemplation ladder tended to be higher for patients who reported smoking cessation at the 6-month follow-up. Previous work in patients with cardiovascular disease demonstrated that patients who identified themselves as being prepared to quit had a higher chance of smoking cessation [20]. Current smokers were more likely to have household contacts who smoked compared to ex-smokers.…”
Section: Discussionmentioning
confidence: 95%
“…Baseline median score on the contemplation ladder tended to be higher for patients who reported smoking cessation at the 6-month follow-up. Previous work in patients with cardiovascular disease demonstrated that patients who identified themselves as being prepared to quit had a higher chance of smoking cessation [20]. Current smokers were more likely to have household contacts who smoked compared to ex-smokers.…”
Section: Discussionmentioning
confidence: 95%
“…Hospitalised patient populations may be highly receptive to such advice, for example one large study revealed as many as 75% of cardiac in-patient smokers are prepared to quit [10]. Therefore, this opportunity while patients are under the care of medical teams should be used to help initiate this important risk factor control, especially as even brief advice may be effective [11].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions implemented in hospitals under the assumption that the patients may be more vulnerable, open and ready to quit smoking at that time, proved to be more effective (Rigotti, Munafo, D. Leontari et al Psychology & Stead, 2008) as the majority of the participants (75%) indicated readiness in quitting smoking. After being advised on smoking cessation, they exhibited increased successful effort probabilities and abstinence maintenance (Shah et al, 2010;Rigotti, Regan, Majchrzak, Knight, & Wechsler, 2002). However, the effectiveness of these interventions has suffered dispute by researchers who claimed that differences in quit rates are not significant (Hennrikus et al, 2005;Hjalmarson & Boethius, 2007).…”
Section: Introductionmentioning
confidence: 99%